Pelatihan Pembuatan Pupuk Organik Limbah Ikan di SMKN 1 Wangi-Wangi - Tamtama, Ary; Nurdiyanti, Iin (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
Fisheries is not becoming important for Indonesias economic resources due to lack of appropriates on potential management by government and sociaty. This is owing to the fact that sea commodities, such as fish becomes in valuable commodity. In addition, fish is one of fisheries product which cattegories as most perishable food. Base on the statistics, there every season is between 25-30% fisheries captures which eventually become waste. There are several reason why it intensifies: limitation of knowledge and equipment in fish processing. Waste derived from capture fishing can be procces in to fertilizer. Therefore we initiate the community service program in order to carry out the problem. This program was conducted at SMKN 1 Wangi-wangi in regency of Wakatobi for four days in August 2015, by using conceling and workshop method. The result of this program show that students were able to comprehend the materials theorically and practice on production on organic fertilizer from fish waste. The student were also able to produce organic fertilizer independently. Additionally, this technic has become complementary skill for the student of SMKN 1 Wangi-wangi, and it is expected to be included in curriculum in SMKN 1 Wangi-wangi